Role of Intermittent Fasting, Calorie Restriction and Autophagy in Healthy Aging: A Review of Literature (Bangladesh Journal of Neuroscience, 2019)
Aging is a progressive process associated with decline in structure and function, hindered maintenance and repair systems, increased vulnerability to disease and death, and reduced reproductive capacity. Healthy aging can be prolonged by calorie limitation or by pharmacologic agents that mimic the effects of caloric restriction. Both fasting and the genetic inactivation of nutrient signaling converge on the induction of autophagy, a cytoplasmic recycling process that counteracts the age-associated accumulation of damaged organelles and proteins as it improves the metabolic fitness of cells. Holy Quran made it compulsory for all healthy adult Muslim to fast during Arabic month of Ramadan from early dawn to dusk. Believers of other religions also have the tradition of fasting as religious rituals in different way. The importance offasting and the autophagy process was highlighted very recently by Prof. Yoshinori Ohsumi, a Noble prize winner in medicine for his pioneering studies revealing the mechanisms of autophagy in baker’s yeast 30 years ago. Here we made literature search to review experimental findings on intermittent fasting (IF) and autophagy that influences the major nutrient and growthrelated signaling pathways as well as the up regulation of anti-aging pathways.Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 39-45